Edaravone in Digestive Diseases – A Narrative Review - Lei H; Wang M; Huang M; Fu X (Drug Design, Development and Therapy, 2025)
Haiyun Lei,* Mingchun Wang,* Ma Huang,* Xiaoyun Fu Department of Critical Care Medicine, Affiliated Hospital of Zunyi Medical University, Zunyi, Guizhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaoyun Fu, Department of Critical Care Medicine, Affiliated Hospital of Zunyi Medical University, Zunyi City, Gui Zhou, People’s Republic of China, Email zyyxyfxy@163.comAbstract: Digestive diseases represent a diverse and complex group of systemic disorders, often marked by intricate pathogenic mechanisms and substantial rates of morbidity, disability, and mortality. While effective therapies exist for certain conditions, such as peptic ulcers, gastrointestinal hemorrhage, and viral hepatitis, many others remain difficult to manage due to their limited treatment options, poor response to current therapies, and multifactorial etiologies. As a result, there is a pressing need to develop novel therapeutic agents that offer greater specificity and improved clinical outcomes. Edaravone, a free radical scavenger widely used in the management of neurological disorders, has demonstrated a favorable safety profile and minimal adverse effects. Recent research has expanded our understanding of Edaravone’s pharmacological actions, revealing its broad therapeutic potential beyond the nervous system. Its capacity to neutralize reactive oxygen species, reduce oxidative stress, suppress inflammation, inhibit apoptosis, modulate immune function, and enhance tissue repair positions it as a promising candidate for treating digestive disorders. This review highlights current advances in the application of Edaravone in digestive disease models and clinical settings, to offer new perspectives for future prevention, therapeutic strategies, and scientific investigation in this field. Keywords: digestive diseases, edaravone, oxidative stress, inflammation, survival